2021
DOI: 10.21203/rs.3.rs-172177/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fear and Depression during the COVID-19 Outbreak in Cameroon: A Nation-wide Observational Study

Abstract: Background: The COVID-19 pandemic has been associated with significant psychological and social distress worldwide. We investigated fear and depression among adults in Cameroon during different phases of the COVID-19 outbreak.Methods: An online survey was conducted in Cameroon from June–December 2020 using a structured questionnaire. Socio-demographic data and information regarding COVID-19 history were obtained. Fear and depressive symptoms were assessed using the Fear of COVID-19 score (FCV-19S) and the Pati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Marital status (i.e., being single, widowed, divorced, or separated) ( 59 , 67 , 79 ), living alone without family or having a lack of emotional support from family and society ( 71 , 97 ) ( 45 , 46 ), family size ≥ 3 ( 48 , 49 ) and living in an urban area ( 31 , 32 , 69 ) were found to significantly increase depression, with the exception of two studies ( 47 , 60 ) which indicated that married people were more than three times as likely to experience depression ( p < 0.05). Higher educational level and professional qualification were found to significantly increase depression ( 29 , 31 , 49 , 59 , 60 , 69 ) with the exception of one study, which indicated higher depressive symptoms among non-educated people with disability (AOR = 2.12, 95% CI: 1.12–5.90) ( 67 ). Unemployment (AOR = 2.1, 95% CI: 1.32–5.11) ( 67 ) and low socioeconomic status significantly influenced the prevalence of depressive symptoms ( 35 , 48 , 49 , 57 , 69 ).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Marital status (i.e., being single, widowed, divorced, or separated) ( 59 , 67 , 79 ), living alone without family or having a lack of emotional support from family and society ( 71 , 97 ) ( 45 , 46 ), family size ≥ 3 ( 48 , 49 ) and living in an urban area ( 31 , 32 , 69 ) were found to significantly increase depression, with the exception of two studies ( 47 , 60 ) which indicated that married people were more than three times as likely to experience depression ( p < 0.05). Higher educational level and professional qualification were found to significantly increase depression ( 29 , 31 , 49 , 59 , 60 , 69 ) with the exception of one study, which indicated higher depressive symptoms among non-educated people with disability (AOR = 2.12, 95% CI: 1.12–5.90) ( 67 ). Unemployment (AOR = 2.1, 95% CI: 1.32–5.11) ( 67 ) and low socioeconomic status significantly influenced the prevalence of depressive symptoms ( 35 , 48 , 49 , 57 , 69 ).…”
Section: Resultsmentioning
confidence: 87%
“…Anxiety prevalence was significantly associated with depression or depressive symptoms ( 35 , 40 , 50 ). Other anxiety-related symptoms reported were insomnia ( 14 , 27 , 40 , 54 , 60 , 65 , 67 , 70 , 72 , 77 , 81 ), fear of covid ( 29 , 53 , 92 ), psychological distress ( 30 ), worry ( 38 ), and fear of getting sick ( 93 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, some regional reports described a nonsignificant increase in depression during the COVID-19 pandemic [ 21 ]. In an online survey in Cameroon, fear and depressive symptoms were high in participants with a history of quarantine, flu-like symptoms, and fear of COVID-19, while adequate COVID-19 information reduced the odds for depression [ 21 ]. In line with these results, another online survey predicted that the participants with viral symptoms and pre-existing mental health problems had a greater risk of depression [ 22 ].…”
Section: Discussionmentioning
confidence: 99%